Long-Term Outcomes of Rheohaemapheresis in the Treatment of Dry Form of Age-Related Macular Degeneration - Jan Studnička; Eva Rencová; Milan Bláha; Pavel Rozsíval; Miriam Lánská; Vladimír Bláha; Jan Němčanský; Hana Langrová (Journal of Ophthalmology)
Purpose. Determining long-term effects of rheohaemapheresis on the dry form of age-related macular degeneration. Methods. This study evaluates 19 patients, average age of 67.6 years, treated with rheohaemapheresis and 18 patients, average age of 72.8 years, comprising the control group. Minimum follow up period was 3.5 years. Each treated patient received a series of 8 sessions of rheohaemapheresis of 1.5 plasma volumes within 10 weeks. We measured the drusenoid pigment epithelium detachment (DPED), best-corrected visual acuity (BCVA), electroretinography (ERG), and rheological parameters. Results. In the treatment group, the baseline BCVA was 0.74 (0.36–1.0) 95% CI and BCVA after 3.5 years was 0.79 (0.41–1.0) 95% CI (P=0.726). In the control group, the baseline BCVA was 0.71 (0.15–1.0) 95% CI and BCVA after 3.5 years decreased to 0.7 (0.32–0.87) 95% CI (P=0.031). Baseline DPED was 6.78 ± 3.79 mm2; after 3.5 years, it decreased to 4.13 ± 3.84 mm2 (P<0.001). In the control group, the baseline DPED was 4.09 ± 3.48 mm2; after 3.5 years, it increased to 6.69 ± 4.2 mm2 (P=0.001). We noted increasing levels of positive wave peaking at 50 milliseconds (P50) after treatment (P=0.022) and a stable amplitude of photopic responses of treated patients. Conclusion. Over the long term, rheohaemapheresis reduced the DPED, improved the function of photoreceptors, and prevented the decline of BCVA.